Phrase frames in English pharmaceutical discourse: a corpus-driven study of intra-disciplinary register variation - Grabowski, Łukasz (Research in Language, 2015)
Focusing on the exploration of intra-disciplinary register variation in the pharmaceutical domain, this corpus-driven study attempts to describe the use, composition and discourse functions of phrase frames, that is, contiguous sequences of words identical except for one (Fletcher, 2002-2007), found in samples of four English pharmaceutical text types, such as patient information leaflets, summaries of product characteristics, clinical trial protocols and chapters/sections from academic textbooks on pharmacology. The study deals with a specific sub-type of phrase frames, that is, 4-word units with a variable slot in the medial position, e.g. be * with caution, to take * medicine. The results showed, among others, that the use and discourse functions of phrase frames vary across pharmaceutical text types, that the correlation between the frequency of phrase frames and their pattern variability may depend on a register or genre, and that it is justified to treat the discourse functions of phrase frames as distinct from those of their textual variants.